2011
DOI: 10.1369/0022155411433331
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 Is Differentially Expressed in Human Embryonic Stem Cells and in Cell Progeny of the Three Germ Layers

Abstract: The secreted glycoprotein YKL-40 participates in cell differentiation, inflammation, and cancer progression. High YKL-40 expression is reported during early human development, but its functions are unknown. Six human embryonic stem cell (hESC) lines were cultured in an atmosphere of low or high oxygen tension, in culture medium with or without basic fibroblast growth factor, and on feeder layers comprising mouse embryonic fibroblasts or human foreskin fibroblasts to evaluate whether hESCs and their progeny pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…YKL-40 plays several roles in different biologic processes such as inflammation, cell proliferation and differentiation, angiogenesis, apoptosis, and regulation of extracellular tissue remodeling (3,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), processes important for the progression of cancer growth and metastatic potential (21). YKL-40 upregulates VEGF expression and blockade of YKL-40 activity decreases tumor growth, angiogenesis, and metastasis in xenografted SCID mice (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…YKL-40 plays several roles in different biologic processes such as inflammation, cell proliferation and differentiation, angiogenesis, apoptosis, and regulation of extracellular tissue remodeling (3,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), processes important for the progression of cancer growth and metastatic potential (21). YKL-40 upregulates VEGF expression and blockade of YKL-40 activity decreases tumor growth, angiogenesis, and metastasis in xenografted SCID mice (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…YKL-40 is a highly conserved glycoprotein produced by cancer cells (including colorectal cancer cells), macrophages and neutrophils (3) and by fetal and embryonic stem cells (9,10). IL6 and hypoxia stimulate YKL-40 synthesis (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, findings based on human samples are very important in order to understand normal brain development and disorders of the central nervous system. So far, YKL-40 has been described particularly in diverse pathological conditions and promoted as a factor with profound implications for both diagnostic and therapeutic applications (Prakash et al 2013), whereas the general role of YKL-40 in developmental biology has been largely ignored, with a few exceptions (Johansen et al 2007;Brøchner et al 2012). In order to elucidate its possible functions during brain development, we have focused on YKL-40 protein and its mRNA expression in human embryonic and fetal forebrain.…”
Section: Ykl-40 In the Early Developing Human Forebrainmentioning
confidence: 99%
“…However, what has not really been emphasized so far, is the lack of EMT in the initial differentiation of epiblast cells directly into the remaining ecto-and neuroectodermal germ layer -an in vivo process of Epiblast-ectodermal transformation (EET) corresponding to an in vitro process of ESC-ectodermal transformation. In a previous in vitro study of regional differences in the expression of markers during differentiation of hESC lines (LRB001-004), we noticed a distinct and direct transformation from undifferentiated OCT4 positive hESCs to SSEA1-positive fully differentiated epithelial cells (Laursen et al, 2007), and in a very recent investigation of six different LRB-cell lines we observed a similar abrupt transformation between OCT4-positive hESC regions and areas with either ectodermal p63-positive cells or neuroectodermal nestinpositive cells, while a direct transition into either meso-or endodermal marker positive cells, was not seen (Brøchner et al, 2011). In the present in vitro study we found an OCT4-postive epithelial-like cell type with a well-defined junctional complex facing the outside compartment which strongly resemble an in vivo embryonic epiblast cell type, whereas the pluripotent cells without junctional complexes in the central compartment of early cultures resemble an ICM-like cell type.…”
Section: Discussionmentioning
confidence: 66%